The Trapezoidal Khim: Sound Radiation of G Notes - Natcha Techaaphonchai; Worakrit Thida; Kittipitch Meesawat; Phonlasit Thinnakorn na ayuthaya; Pakaphol Chitsakul; Sorasak Danworaphong (My University, 2025)
This research investigates the sound characteristics of the trapezoidal Khim, a traditional Thai hammered dulcimer, focusing on the G 196, G 392 Hz and G 784 Hz notes played with different hammers. Two types of wooden hammers were used, that is, covered with flannel and uncovered. Measurements were conducted in a room measuring 10 by 5 by 3 meters using two microphones, one for capturing the sound field directionality and the other for reference sound. The measurement microphone was placed 2 meters away from the instrument at various angles, while the reference microphone was positioned above the center of the instrument. Analysis of the recordings reveals the directivity profiles for each frequencies, showing that the Khim exhibits relatively high directivity at 90 and 270 degrees, corresponding to its open channels of the instrument. This suggests that the instrument's construction significantly influences its sound radiation. Hammer type was found to affect overall directivity, i.e., fabric-covered hammers resulted in lower directivity compared to uncovered hammers. Furthermore, the hitting point on the key significantly affects the Khim's directivity, indicating that playing technique plays a crucial role in shaping the instrument's sound projection. This study contributes to a deeper understanding of the unique sound production of the trapezoidal Khim and its role in traditional Thai music. It offers valuable information for musicians, instrument makers, and researchers interested in the acoustics of cultural instruments in realistic performance environments.
Keywords: Linguistics and Cultural Studies